Infant Mandibular Distraction for Upper Airway Obstruction: A Clinical Audit. Issue 7 (July 2016) - Adhikari, Ashim N.; Heggie, Andrew A.C.; Shand, Jocelyn M.; Bordbar, Patrishia; Pellicano, Anastasia; Kilpatrick, Nicky
Abstract : Background: Mandibular distraction osteogenesis (MDO) is an effective method of treating upper airway obstruction (UAO) in micrognathic infants. The short-term outcomes include relief of UAO, avoidance of tracheostomy, and prompt discharge from hospital. However, it is a significant surgical procedure with potential associated morbidities. This study describes a cohort of infants managed using MDO over a twelve-year period. Methods: A retrospective chart review was undertaken for children who had MDO before the age of 5 years between 2000 and 2012. This was followed by a clinical review of the same cohort specifically looking for dental anomalies, nerve injuries, and scar cosmesis. Results: Seventy-three children underwent MDO at a mean age of 2 months [interquartile range (IQR), 1.7–4.2] for nonsyndromic infants and 3.3 months (IQR, 2.1–7.4) for those with syndromes. Infants were discharged from hospital, on average, 15 days after procedure. After MDO, of the 9 who were previously tracheostomy dependent, 5 (56%) were decannulated within 12 months and none of the nontracheostomy-dependent children required further airway assistance. The majority of children required supplemental feeding preoperatively but, 12 months postoperatively, 97% of the nonsyndromic infants fed orally. Thirty-nine children (53%) were reviewed clinically [median age, 5.1 y (IQR, 3.9–6.5)] with 18 being syndromic. Many of the mandibular first permanent and second primary molars had developmental defects, but there was a low rate of neurosensory deficit and good scar cosmesis. Conclusions: This study contributes further to the evidence base underpinning the management of micrognathic infants with UAO.